Självförvaltningens effekter i vår gemensamma utemiljö - Johansson, Emma (SLU/Landscape Architecture (until 121231), 2010)
When we, in the turn of the year 07/08 moved to Holma, Malmö, I and my cohabiter immediately joined the self-management on our tenement yard, partly because we both missed having a garden since we moved to an apartment, partly because of the rent reduction. The aim with this thesis is to examine how the common outdoor environment in tenement yards is affected when the tenets themselves are responsible for the maintenance. But also to see what social affects self-management brings. The purpose is to increase the understanding of how self-management works in practice and how we as landscape architects need to adjust ourselves and our design to create a lasting design that works when the tenets are in charge of their own outdoor environment. I have been studying a number of tenement yards with selfmanagement, both municipal and private tenement houses. I have studied both their design and their self-management, how it is working and how it is organized partly trough deep interviews and also by questionnaires to the tenets of the yards in question. I found three tenement yards with some differences. Fosiedal is a yard with terrace houses, with the oldest self-management and it’s existed since 1985. Many families with children live here who use the yard for both playing and recreation. The yard is well adapted for everyone with multiple playgrounds, a soccer field, a basketball field and lots of benches. The design and maintenance of the yard is to most tenets satisfaction. Nydala is a million program area from the 1960s. They have had self-management since 1977 with the same coordinator. Quite a few single adults live here and many do not use the yard at all. But the once that do they do so to see ones neighbour, to relax or to work in the garden. Ystadsgatan 13 is a bit different as the tenement yard lies completely private inside the house, behind a locked gate, a stone’s throw from Möllevångstorget. There are 14 apartments and the self-management is completely voluntary and does not give any rent reduction, rather the other way round. The yard which is completely covered with asphalt is since 2002 a green paradise thanks to interested tenets. The result from the poll and from the deep interviews where the importance of a good and consistent coordinator who is engaged in the yard and its tenets, who successfully plan and organizes the work together with the tenets. The number one reason to get involved in the self-management is to socialize with the neighbours, other reasons is that it is a pleasant occupation or so that the yard would be properly maintained. Some of the tenets also think that it is very important to be able to influence the design of the yard. Landscape architects needs to see the benefits and possibilities with self-management and how to proceed to get the best result when designing a tenement yard with self-management. To create a green durable frame that allows changes in perennials and annuals and tempt and encourage to creativity is preferable. Areas that can easily be altered to fit the number of tenets engaged are also preferable as it can vary substantially.